Agreement and reliability of lower limb muscle architecture measurements using a portable ultrasound device - Ritsche, Paul; Schmid, Reto; Franchi, Martino; Faude, Oliver (Current Issues in Sport Science (CISS), 2023)
Although ultrasonography is commonly used to assess muscle architecture, high-end ultrasonography devices lack in portability and are expensive. Recently, ultrasonography devices consisting solely of a probe, an app, and/or a mobile display were introduced. These devices have lower acquisition costs than high-end devices and demonstrate higher portability. Portable systems would allow for cost-effective, on-site athlete or patient screenings of muscle architecture as well as diagnosis of pathologies or injury. Furthermore, portable systems can be easily transported to allow for uncomplicated assessment of athletes belonging to different teams or patients in different hospital units. Nonetheless, the reliability of portable systems and the comparability to high-end devices for muscle architecture assessment have not been investigated. We investigated the agreement and reliability of a portable and handheld ultrasonography system for muscle architecture measurements in human lower limb muscles. We acquired images of the rectus femoris (RF), vastus lateralis (VL) and gastrocnemius medialis (GM) in 36 active healthy participants (15 female, 21 male) at 50% of muscle length using the handheld Lumify (L12-4, linear array 37 mm, Philips Healthcare, Amsterdam, Netherlands) and a high-end laboratory device (ACUSON Juniper, linear-array 54 mm, 12L3, SIEMENS Healthineers, Erlangen, Germany). Muscle length was determined as distance between the proximal and distal muscle tendon junction. We compared measurements of muscle fascicle length, pennation angle and thickness. To assess inter-session reliability of the Lumify system, participants were measured twice within 1 week. Comparing RF architecture measurements of both devices resulted in intra-class correlations (ICCs) ranging from 0.46–0.82 and standardized mean difference (SMDs) ranging from −0.45–0.05. For VL, ICCs ranged from 0.60–0.89 and SMDs ranged from −0.11–0.13. ICCs and SMDs for the GM ranged from 0.82–0.86 and −0.07–0.07. Calculating inter-session reliability for RF resulted in ICCs ranging from 0.44–0.76 and SMDs ranging from −0.38–0.15. For VL, ICCs and SMDs ranged from 0.57–0.75 and −0.13–0.02. ICCs for GM ranged from 0.75–0.92 and SMDs ranged from −0.15–0.16. The highest agreement (ICC ≥ 0.82) and reliability (ICC ≥ 0.75) across all muscles was demonstrated for the measurement of muscle thickness. The Lumify system was comparable to a high-end device and reliable for GM measurements. Nevertheless, agreement and reliability were lower for the RF and VL. Thus, when interpreting longitudinal observed changes in muscle architecture assessed with the Lumify system, measurement errors should be considered. Future investigations should consider including different participant populations, comparing the reliability of different portable systems for muscle architecture assessment as well as including different muscle groups.